Aplastic anemia in pregnancy: Case report and review of the literature - Sepúlveda-Rivera, Cintia María (2019)
We present the case of a pregnant woman with aplastic anemia. The 22-year-old patient presented with 27 weeks of gestation and lymphoproliferative syndrome at the Instituto Nacional de Perinatología in Mexico City. The bone marrow biopsy confirmed the diagnosis and the immunophenotype was negative for malignancy. The treatment consisted of transfusions and planned birth at 35 weeks. Afterwards, the patient was referred to a bone marrow transplant unit.